İNSAN ÜZERİNDE BİRİKTİRİLEN ELEKTROSTATİK YÜKLERİN FİZYOLOJİK VE PSİKOLOJİK ETKİLERİ - KÖRPINAR, Mehmet Ali (Cerrahpaşa Medical Journal, 2019)
Background and Design.- In this study our aim was to investigate the physiological and psychological effects of "accumulated" electrostatic load on humans and to postulate probable solutions to overcome these effects, if any. In this study 17 healthy male subjects (ages 16-18 years) were seated in a quite environment for 15 minutes and pre-experimental measurements were carried out as outlined below. For the measurement of the reaction to light and sound, the subjects were seated comfortably and requested to answer the questions related to the light and sound stimuli which were generated by the Miernik Raekeji MRK-433 model reaction time measurement device. For the measurement of the short-term memory, the subjects were requested to repeat a sequence of minimum 3, maximum of 9 digit numbers both forward and backwards and the number of errors were recorded. The stable anxiety inventory tests the anxiety level of the subjects. Two types of answer keys exists, which display the anxiety level and the numerical results obtained through these keys respectively were used to evaluate the anxiety levels of the subjects. The data obtained through the subjects under ( + ), (-), and neutral conditions were compared with the data obtained pre-experimentally by using the Student's t-test. Results.- While ( +) electrostatic field was found to be increasing all the physiological parameters (systolic and diastolic blood pressure, reaction to sound and light, rate of hand sweating) except the heart-beat rate, the reverse of that was true for the (-) electrostatic field (p<0.05). Likewise, while the positive field was found to be decreasing the short-term memory (numbers of errors) significantly, the negative field increased this ability and neutral field had no significant effect All types of electrostatic loadings were found to have no effect on the stable anxiety inventory. Conclusion.- Thus, it will not be wrong to state the fact that positively charged electrostatic fields cause stress and have harmful effects on humans, while the negatively charged fields ease out the stress and might even have a beneficial effect.